Optical detection of nanoparticle agglomeration in a living system under the influence of a magnetic field - Mueller, Robert; Stranik, Ondrej; Schlenk, Florian; Werner, Sebastian; Malsch, Daniell; Fischer, Dagmar; Fritzsche, Wolfgang (Journal of Magnetism and Magnetic Materials, 2015)
Nanoparticles are important in diagnosis and therapy. In order to apply their potential, an understanding of the behavior of particles in the body is crucial. However, in vitro experiments usually do not mimic the dynamic conditions of the in vivo situation. The aim of our work was an in vivo observation of particle transport in chicken egg vessels in the presence of a magnetic field by particle tracking. For that we demonstrate the spatial resolution of our observations in a vein and a temporal resolution by observation of the cardiac cycle in an artery. Microscopic images were recorded in dark field reflection and fluorescence mode.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Agglomeration; Chick area Vasculosa; Magnetic particles; Particle transport